Islamic Bank NPF Prevention Strategy in Indonesia - Aulia Nur Cahyani (Ekonomi Islam Indonesia, 2019)
Financing is one of the activities of channeling funds carried out by Islamic banks, one of the Islamic banks is Islamic rural banks (BPRS). Risk arising from financing is default risk assessed by the ratio of Non Performing Financing (NPF). BPRS in the area of Kabupaten Bogor have NPF values above the safe limit set by Bank Indonesia. The purpose of this study is to identify the causes and solutions to default financing and formulate strategies for preventing default financing of BPRS in Kabupaten Bogor. The method used in this study is Delphi method. The result showed that external cause is the most influential factor towards the occurrence of default financing. The most influential internal cause is the lack of analyzing capability of HR (human resources). The most influential external cause is the customer’s business which getting worse. External solution is the priority solution that need special attention. Internal solution that is prioritized is internal supervision from the head of financing. The priority external solution is educating and monitoring the use of funds. The priority of the default financing prevention strategy in this study is visiting the customers routinely.